2020
DOI: 10.1111/tbj.14047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interval breast cancers with 2D digital mammography versus 3D digital breast tomosynthesis in a large community‐based practice

Abstract: Incidence of interval cancers is an important outcome in assessing efficacy of screening. Our primary objective was to compare the incidence of interval cancers detected with two‐dimensional digital mammography (DM) versus digital breast tomosynthesis (DBT) in a large community health system. Our secondary objectives were to compare the patient and tumor characteristics of interval cancers, cancer detection rate, and recall rate. Interval cancers before and after implementation of DBT (2012‐2014 DM group; 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Our finding of no statistically significant difference in interval cancer rate between screening with DBT+SM versus DM is in keeping with most other studies(104,157,159,160,(162)(163)(164). One exception is MBTST, in which a statistically significant lower interval cancer rate for women screened with DBT compared with a historical cohort screened with…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Our finding of no statistically significant difference in interval cancer rate between screening with DBT+SM versus DM is in keeping with most other studies(104,157,159,160,(162)(163)(164). One exception is MBTST, in which a statistically significant lower interval cancer rate for women screened with DBT compared with a historical cohort screened with…”
supporting
confidence: 90%
“…cancer detected after screening with DBT+SM versus DM. Few other studies report on histopathological tumor characteristics for interval cancer after screening with DBT, and those who do are mainly in line with our study(104,160,161,163).One major challenge concerning interval cancer and DBT is that interval cancer rates in general are low, which require larger study populations than what is published to reach statistical significance at the observed rates. Due to our large study sample and almost 100% completeness of the database at the Cancer Registry of Norway on interval cancer, our study has one of the highest number of interval cancers (n=156) among the published studies.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…For improved interpretation of the increased CDR, cancer biology and results for different breast densities may play a role. While Winter et al [ 36 ] reported a lower rate of node positive interval cancers after DBT screening, Bahl et al [ 37 ] reported comparable biology of interval cancer after DBT versus FFDM. Both of these study designs, however, cannot exclude bias.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mammography and ultrasonography do have some drawbacks in detecting early-stage BC, such as lower sensitivity in younger women or in women with higher breast density [ 3 , 4 ]. In addition, mammography screens are planned at fixed time intervals, but non-predicted interval cancers may occur between two screens [ 5 ]. Moreover, experienced radiologists are required to analyse mammography results [ 4 ] as well as to carry out MRI scans, which are also very time-consuming, costly and impractical to be performed routinely.…”
Section: Introductionmentioning
confidence: 99%